Modulation of the Plasma Kallikrein-Kinin System Proteins Performed by Heparan Sulfate Proteoglycans - Motta, Guacyara; Tersariol, Ivarne L. S. (Frontiers in Physiology, 2017)
Human plasma kallikrein-kinin system proteins are related to inflammation through bradykinin. In the proximity of its target cells, high molecular weight kininogen (H-kininogen) is the substrate of plasma kallikrein,which releases bradykinin from H-kininogen. Heparan sulfate proteoglycans (HSPGs) play a critical role in either recruiting kinin precursors from the plasma, or in the assembly of kallikrein-kinin system components on the cell surface. Furthermore, HSPGs mediate the endocytosis and activation of H-kininogen and plasma prekallikrein. In the presence of HSPGs (Chinese hamster ovary cell, CHO-K1, wild type cells) both heparin and heparan sulfate strongly inhibit the H-kininogen interaction with the cell membrane. H-kininogen is internalized in endosomal acidic vesicles in CHO-K1 but not in CHO-745 cells (mutant cells deficient in glycosaminoglycan biosynthesis).The endocytosis process is lipid raft-mediated and is dependent on caveolae. Both types of CHO cells do not internalize bradykinin-free H-kininogen. At pH 7.35, bradykinin is released from H-kininogen on the surface of CHO-745 cells only by serine proteases; however, in CHO-K1 cells either serine or cysteine proteases are found to be involved. The CHO-K1 cell lysate contains different kininogenases. Plasma prekallikrein endocytosis in CHO-K1 cells is independent of H-kininogen, and also prekallikrein is not internalized by CHO-745 cells. Plasma prekallikrein cleavage/activation is independent of glycosaminoglycans but plasma kallikrein formation is more specific on H-kininogen assembled on the cell surface through glycosaminoglycans. In this mini-review, the importance of HSPGs in the regulation of plasma kallikrein-kinin system proteins is shown.